(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study is to estimate the high availability of Query processing using Novel Docker Container over kubernetes micro service architecture. Materials and Methods: Sample groups that are considered in the project can be classified into two each has 20 samples, one for Microservice architecture and other for Novel Docker container, which are tested using 0.80 for G-power to determine the sample size and for t-test analysis. 20 queries have been used in each group for estimating high availability. Results: The Novel Docker container with efficient accuracy of 91.10%, which by far seems to be better than the kubernetes based micro service architecture which gives around 87.50%. As a result, the study group has a statistically negligible difference. The significance is around 0.039 (p<0.05) and therefore there is a statistical insignificant difference among the study group. Conclusion: The query processing speed in the Novel Docker container is better compared to kubernetes based micro service architecture.